The effect of Nigella Sativa emulgel on episiotomy wound healing and pain intensity in primiparous women: A triple-blind randomized controlled trial - Mahsa Maghalian; Afsaneh Alizadeh; Fatemeh Raphi; Ziba Islambulchilar; Laleh Khodaie; Mahsan Nabighadim; Simin Taghavi; Mojgan Mirghafourvand (PLoS ONE, 2025)
Background Episiotomy, a common surgical procedure during childbirth, often leads to complications such as pain, infection, and delayed healing. Nigella sativa has demonstrated anti-inflammatory and wound-healing properties in prior studies and have received United States Food and Drug Administration (FDA) approval for food use, indicating their safety. This study aimed to evaluate the efficacy of Nigella sativa emulgel on episiotomy wound healing and pain intensity in primiparous women. Methods A triple-blind, randomized controlled trial was conducted at Taleghani Hospital, Tabriz, Iran (May 2023–April 2024). Seventy-four primiparous women with mediolateral episiotomy were randomized to receive either Nigella sativa emulgel or placebo, applied topically three times daily for 7 days post-discharge. Wound healing was assessed using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, Approximation; primary outcome), and pain intensity was measured via visual analog scale (VAS; secondary outcome). Outcomes were evaluated at discharge (baseline) and 10 ± 1 days postpartum. Data were analyzed using independent t-tests, ANCOVA (adjusted for baseline scores), and Mann-Whitney U tests for non-normal distributions (SPSS v26). Results At 10 ± 1 days postpartum, the Nigella sativa group showed significantly better wound healing (REEDA score: MD −0.79, 95% CI −1.20 to −0.39; p = 0.001) and lower pain scores (VAS: MD −0.74, 95% CI −1.3 to −0.11; p = 0.021) compared to placebo. Subscale analysis revealed improvements in redness (p = 0.037), edema (p = 0.041), and ecchymosis (p = 0.043). No adverse effects were reported, and satisfaction was higher in the Nigella sativa group (86.5% vs. 56.7%; p = 0.046). Conclusions Topical Nigella sativa emulgel significantly improved episiotomy wound healing and reduced pain intensity, with high patient satisfaction. These findings support its potential as a natural therapeutic option, though larger multi-center trials are needed for broader validation. Trial registration Iranian Registry of Clinical Trials IRCT20120718010324N68.